2004
DOI: 10.1002/ange.200460663
|View full text |Cite
|
Sign up to set email alerts
|

Cavity Effects on the Enantioselectivity of Chiral Amido[4]resorcinarene Stereoisomers

Abstract: Ein starker Effekt der Größe und der hydrophilen/hydrophoben Eigenschaften von Kavitäten auf die Reaktionskinetik und ‐dynamik wird bei der Gasphasenreaktion von (R)‐(−)‐2‐Butylamin mit Komplexen stereoisomerer Amido[4]resorcinaren‐Wirte mit aromatischen Aminosäuren deutlich. Das Diagramm zeigt den kinetischen Verlauf der baseninduzierten Verdrängung von L‐Phe (grün), L‐Tyr (rot) und L‐Dopa (blau).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 16 publications
1
20
0
Order By: Relevance
“…The reaction plots of the enantiomeric ␤-amino acids show bimodal behavior showing the existence of fast (k fast ) and slow (k slow ) reacting complexes. The reason for this kind of behavior might be due to possibility that more than one ion population is present and/or there are some "hot" segments in ion population, which are reacting quickly away [34,42]. This same kind of behavior was also observed in our earlier studies of differentiation of diastereomeric ␤-amino acids, for example cyclopentane and cyclohexane ␤-amino acids, when host-guest complexes and ion/ molecule reactions were utilized [38,43].…”
Section: Differentiation Of Enantiomeric 2-aminocyclohexanecarboxylicsupporting
confidence: 66%
“…The reaction plots of the enantiomeric ␤-amino acids show bimodal behavior showing the existence of fast (k fast ) and slow (k slow ) reacting complexes. The reason for this kind of behavior might be due to possibility that more than one ion population is present and/or there are some "hot" segments in ion population, which are reacting quickly away [34,42]. This same kind of behavior was also observed in our earlier studies of differentiation of diastereomeric ␤-amino acids, for example cyclopentane and cyclohexane ␤-amino acids, when host-guest complexes and ion/ molecule reactions were utilized [38,43].…”
Section: Differentiation Of Enantiomeric 2-aminocyclohexanecarboxylicsupporting
confidence: 66%
“…Speranza applied ESI-MS n CID and REMPI-TOF methodologies to measure the fragmentation thresholds of diastereomeric clusters [19,23,25,32,48,49]. They found that the chiral recognition was very sensitive to cavity size and hydrophilic/hydrophobic properties of the chiral receptor [24,50]. The same group also used gas-phase guest exchange reactions between diastereomeric adducts and chiral or achiral reactants [27,[51][52][53].…”
mentioning
confidence: 99%
“…With the aim to outline a comprehensive study of the tetramide/nucleosides interaction, we performed a complete [12][13][14][15][16][17] [18].…”
Section: Esi-ft-icr Experimentsmentioning
confidence: 99%